Generasi Bersinar bagi Indonesia Emas 2045: Pembekalan Berdasarkan Matius 5:16 bagi Para Murid PPA Efrata ID0524 di Kampung Nanas, Samarinda - Paulus Dimas Prabowo (Journal Of Social Empowerment Publications, 2024)
Indonesia initiated the vision of Indonesia Emas 2045 with an optimistic tone, but there are major challenges that are also present, such as increasing social complexity and moral decline that encourage cultural and spiritual values. The same anxiety was also felt by the mentors of the Efrata ID0524 Child Development Project (PPA) in Samarinda. One solution is to provide training on the basic principles for forming a generation that is able to be a light in the midst of the darkness of the times based on Matthew 5:16. The purpose of this activity is to equip PPA Efrata ID0524 students to become a 'Shining Generation' who are ready to contribute to Indonesia Emas 2045. The activity was held on November 4, 2024 at GBT Yesus Alfa Omega, Bukuan Village, Palaran District, Samarinda City. The number of attendees was 158 people consisting of mentors, students fostered by PPA ID0524 Samarinda aged 5-20 years, and parents of students. The method of briefing is through lectures interspersed with interactions. The briefing material is based on Matthew 5:16. The method of writing this PkM article is literature study and exegesis. The results of the briefing showed positive things, both in terms of enthusiasm and commitment from the participants.